Generalized colloidal synthesis of high-quality, two-dimensional cesium lead halide perovskite nanosheets and their applications in photodetectors. Issue 28 (5th July 2016) - Lv, Longfei; Xu, Yibing; Fang, Hehai; Luo, Wenjin; Xu, Fangjie; Liu, Limin; Wang, Biwei; Zhang, Xianfeng; Yang, Dong; Hu, Weida; Dong, Angang
Abstract : A generalized colloidal approach has been developed to directly synthesize high-quality CsPbX3 (X = Cl, Br, and I) perovskite nanosheets. Abstract : All-inorganic cesium lead halide perovskite (CsPbX3, X = Cl, Br, and I) nanocrystals (NCs) are emerging as an important class of semiconductor materials with superior photophysical properties and wide potential applications in optoelectronic devices. So far, only a few studies have been conducted to control the shape and geometry of CsPbX3 NCs. Here we report a general approach to directly synthesize two-dimensional (2D) CsPbX3 perovskite and mixed perovskite nanosheets with uniform and ultrathin thicknesses down to a few monolayers. The key to the high-yield synthesis of perovskite nanosheets is the development of a new Cs-oleate precursor. The as-synthesized CsPbX3 nanosheets exhibit bright photoluminescence with broad wavelength tunability by composition modulation. The excellent optoelectronic properties of CsPbX3 nanosheets combined with their unique 2D geometry and large lateral dimensions make them ideal building blocks for building functional devices. To demonstrate their potential applications in optoelectronics, photodetectors based on CsPbBr3 nanosheets are fabricated, which exhibit high on/off ratios with a fast response time.